MRCP 1 : Cardiology, Haematology, Respiratory Medicine - Kalra, Paul R. ; Dwight, Jeremy ; McMullin, Mary Frances and et.al (Knutsford PASTEST, 2005)
Part of "MRCP 1 Pocket Book" series, this book features questions and answers providing essential practice for the MRCP Part 1 exam.